2017
DOI: 10.1177/1039856217695706
|View full text |Cite
|
Sign up to set email alerts
|

Where pseudo-hallucinations meet dissociation: a cluster analysis

Abstract: History of childhood trauma and variability in derealisation/depersonalization scores were better predictors of external, negative, uncontrollable voices than diagnosis of BPD or PTSD. The potential links between dissociative states and pseudo-hallucinations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Indeed, prior research has demonstrated a strong correlation in veterans with PTSD between hearing voices and other dissociative experiences both in the present and at the time the traumatic event occurred ( Brewin & Patel, 2010 ). Wearne, Curtis, Genetti, Samuel, and Sebastian (2017) also showed that dissociative experiences (including depersonalisation and derealisation) were a better predictor of AVHs than a diagnosis of PTSD. Both theory and prior research therefore suggest that the experience of AVHs in PTSD may be better understood as a dissociative experience and thus conceptualised as ‘pseudohallucinations’ and we shall use this term for the rest of the current article.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, prior research has demonstrated a strong correlation in veterans with PTSD between hearing voices and other dissociative experiences both in the present and at the time the traumatic event occurred ( Brewin & Patel, 2010 ). Wearne, Curtis, Genetti, Samuel, and Sebastian (2017) also showed that dissociative experiences (including depersonalisation and derealisation) were a better predictor of AVHs than a diagnosis of PTSD. Both theory and prior research therefore suggest that the experience of AVHs in PTSD may be better understood as a dissociative experience and thus conceptualised as ‘pseudohallucinations’ and we shall use this term for the rest of the current article.…”
Section: Introductionmentioning
confidence: 91%
“…For those experiencing civilian PTSD this raises the question of whether particular types of trauma exposure or trauma history are more or less likely to be associated with the experience of pseudo-hallucinations, as we know that dissociation is differentially associated with particular profiles of trauma exposure ( Briere, 2006 ). The experience of childhood sexual abuse, has been established as a predictor of pseudohallucinations in samples both with and without psychosis ( Hammersley & Fox, 2006 ; McCarthy-Jones, 2011 ; Read, McGregor, Coggan, & Thomas, 2006 ; Wearne et al, 2017 ), although the properties of the voices in these populations do not appear to differ between those with and without CSA (e.g. Offen, Waller, & Thomas, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The High severity class exhibited an increased rate of comorbid schizophrenia, which aligns with their increased reporting of hallucinations (Longden et al, 2020; Perona‐Garcelan et al, 2012; Varese et al, 2012) and with the high frequency of dissociative symptoms in schizophrenia (O'Driscoll et al, 2014). There is also a documented relationship between dissociation and a history of trauma in schizophrenia spectrum disorders (Renard et al, 2017) wherein patients with PTSD and schizophrenia with a history of trauma exhibited significantly higher dissociative symptoms as compared to schizophrenic patients with no trauma history (Wearne et al, 2017). The High depersonalization class was characterized by a higher rate of comorbid bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…73 Although complex partial-seizure-like symptoms other than depersonalization/derealization themselves have yet to be explored fully in patients with diagnosed depersonalization disorder, nevertheless, in a sample of patients with BPD or PTSD, depersonalization/derealization symptoms were strongly associated with the presence of pseudohallucinations independent of diagnosis, and scores on the depersonalization subscale of the DES were the most strongly associated with psychotic symptoms. 55,74 DID and OSDD. DID and DID-like presentations of OSDD have been related to severe and prolonged early life trauma.…”
Section: Psychotic-like Symptoms In Trauma-related Disordersmentioning
confidence: 99%